Consideration of organochlorine pesticide levels in water, sediment and fish from Ethiope River at Sapele, Delta State, Nigeria - Edjere, Oghenekohwiroro; Fovwe Ogeleka, Doris; Ebodaghe Okieimen, Felix; Ebehiriemea Ukpebor, Justina (Pure and Applied Science Advances, 2018)
Water, sediment and fish samples from the Ethiope River at Sapele in the Niger Delta region of Nigeria were collected and analyzed for organochlorine pesticide (OCPs) with the aim of ascertaining the level of concentration and distribution of the organochlorine content for the purpose of safe guarding organisms in these matrices. Samples from the three matrices: water, sediment, fish (T. Zilli) were collected in December (dry season) and July (rainy season). 26 OCPs was set out to be investigated, but only 21 was detected. Results from this study revealed the presence of 21 organochlorine pesticide (OCPs) of varying concentrations across the three matrices in Ethiope River. The hazard quotient (HQ) values for all studied site were all between 1 and 10 (1.66, 1.84), this was indicative of moderate hazard contamination; however, that of the bioaccumulation index (BI) for the fish were all greater than 1 (72.426 and 144.996) for rainy and dry season respectively. The distribution of organochlorine pesticides could be associated with land-use practices including agriculture and urbanization. The results suggest the need for sustained monitoring of importation, distribution, usage and disposal of OCPs.